Inhibition of glycogen breakdown by imino sugars in vitro and in vivo. - Andersson, U; Reinkensmeier, G; Butters, T; Dwek, R; Platt, F (2004)
The imino sugar N-butyldeoxynojirimycin (NB-DNJ) is a glucose analogue which inhibits the glycoprotein N-glycan processing enzymes alpha-glucosidases I and II and the ceramide glucosyltransferase that catalyses the first step of glycosphingolipid biosynthesis. This and other N-alkylated DNJ compounds have the potential to inhibit other glucosidase, including acid alpha-glucosidase and alpha-1,6-glucosidase, enzymes involved in glycogen breakdown. We have investigated the effect of NB-DNJ and N-nonyldeoxynojirimycin (NN-DNJ) on glycogen catabolism. Both NB-DNJ and NN-DNJ were potent inhibitors of acid alpha-glucosidase and alpha-1,6-glucosidase in vitro. NB-DNJ and NN-DNJ inhibited liver glycogen breakdown in vivo in fasting mice. Inhibition of glycogen catabolism occurred in the cytosol and lysosomes. The liver glycogen breakdown inhibition was only induced at high doses of NB-DNJ, whereas NN-DNJ caused glycogen accumulation at lower doses. The in vivo effect of NB-DNJ on liver glycogen was transient as there was no inhibition of breakdown after 90 days of treatment. The inhibition by NN-DNJ, was more pronounced, reached a plateau at 50 days and then remained unchanged. Increased glycogen was also observed in skeletal muscle in NB-DNJ- and NN-DNJ-treated mice. Since the effects on glycogen metabolism by NB-DNJ are transient and only occur at high concentrations, it is not predicted that glycogen breakdown will be impaired in patients receiving NB-DNJ therapy. NN-DNJ is the prototype of long alkyl chain derivatives of DNJ that are entering pre-clinical development as potential hepatitis B/hepatitis C (HBV/HCV) therapeutics. Depending on the dose of these compounds used, there is the potential for glycogen catabolism to be partially impaired in experimental animals and man.